Climate change anxiety and symptom severity in individuals with schizophrenia across seasonal variations: a prospective cohort study - Sharbat Mostafa Mohamed; khaled Elbeh; Naglaa Abd Elmeged Mohammed; Nadia Abd El-ghany Abd El-hameed; Gellan K. Ahmed (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Schizophrenia demonstrates complex interactions with environmental factors, including climate change. This study aimed to investigate the relationship between climate change anxiety and symptoms severity among individual with schizophrenia across seasonal variations and it determines. A cohort study was conducted at Assiut University's Psychiatry Hospital, involving 40 individual with schizophrenia and 40 healthy controls. Participants were assessed using multiple tools including the Personality Inventory for DSM-5 (PID-5), Montreal Cognitive Assessment (MOCA), Climate Change Anxiety Scale (CCAS), Symptom Checklist-90-Revised (SCL-90-R), and Positive and Negative Syndrome Scale (PANSS). Data collection spanned a full annual cycle to capture seasonal variations. Results The schizophrenia group showed elevated scores across all personality subscales and lower cognitive function scores than other group. In addition, schizophrenia group exhibited significantly higher climate change anxiety scores compared to controls, with pronounced seasonal variations. Summer presented the highest mean scores for positive symptoms (16.4 ± 5.935), negative symptoms (20.45 ± 5.033), and general psychopathology (39.28 ± 9.597). Medical comorbidity emerged as a significant predictor of climate change anxiety in autumn and winter, while negative symptoms predicted anxiety during winter and spring periods. Conclusions Schizophrenia group experience significant seasonal fluctuations in climate change anxiety, and symptoms, particularly during summer.